Development and characterization of fluorescent cholesteryl probes with enhanced solvatochromic and pH-sensitive properties for live-cell imaging - Vicente Rubio; Nicholas McInchak; Genesis Fernandez; Dana Benavides; Diana Herrera; Catherine Jimenez; Haylee Mesa; Jonathan Meade; Qi Zhang; Maciej J. Stawikowski (Scientific Reports, 2024)
Abstract We present novel fluorescent cholesteryl probes (CNDs) with a modular design based on the solvatochromic 1,8-phthalimide scaffold. We have explored how different modules—linkers and head groups—affect the ability of these probes to integrate into lipid membranes and how they distribute intracellularly in mouse astrocytes and fibroblasts targeting lysosomes and lipid droplets. Each compound was assessed for its solvatochromic behavior in organic solvents and model membranes. Molecular dynamics simulations and lipid partitioning using giant unilamellar vesicles showed how these analogs behave in model membranes compared to cholesterol. Live-cell imaging demonstrated distinct staining patterns and cellular uptake behaviors, further validating the utility of these probes in biological systems. We compared the empirical results with those of BODIPY-cholesterol, a well-regarded fluorescent cholesterol analog. The internalization efficiency of fluorescent CND probes varies in different cell types and is affected mainly by the head groups. Our results demonstrate that the modular design significantly simplifies the creation of fluorescent cholesteryl probes bearing distinct spectral, biophysical, and cellular targeting features. It is a valuable toolkit for imaging in live cells, measuring cellular membrane dynamics, and studying cholesterol-related processes.